2014
DOI: 10.1016/j.jtcvs.2013.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Fontan hemodynamics from 100 patient-specific cardiac magnetic resonance studies: A computational fluid dynamics analysis

Abstract: Fontan power loss varies from patient to patient, and elevated levels are correlated with lower systemic flow and cardiac index. Fontan connection type does not influence hemodynamic efficiency, but an undersized or stenosed Fontan pathway or pulmonary arteries can be highly dissipative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 35 publications
2
90
0
Order By: Relevance
“…Application of 4D flow in a cohort of various Fontan circuit connections revealed different energy loss with different connections (Fig. 4) [32]. Increasing power loss is found to be associated with reduction in aerobic exercise capacity [33].…”
Section: Flowsmentioning
confidence: 94%
“…Application of 4D flow in a cohort of various Fontan circuit connections revealed different energy loss with different connections (Fig. 4) [32]. Increasing power loss is found to be associated with reduction in aerobic exercise capacity [33].…”
Section: Flowsmentioning
confidence: 94%
“…The total cavopulmonary connection (TCPC), created in the last stage of the Fontan procedure, comprises a resistance unit that functions in series with the SV and influences ventricular loading [5][6][7][8]. A number of cross-sectional studies have focused on the interactions between TCPC hemodynamics and the overall circulation [6,9], ventricular function [10,11], venous return [11], and vessel stenosis [12]. However, there are little data on serial evaluation of patient-specific anatomic, hemodynamic, and energetic changes with time.…”
mentioning
confidence: 99%
“…12 This difference is not unexpected given that, by construction, intra-atrial TCPCs typically feature no or little offset, so that the effect of that variable is only weakly present across intra-atrial patients. In fact, when grouping intra-atrial (n = 67) and extra-cardiac (n = 41) TCPCs together, Tang et al 38 demonstrated that IVC-SVC offset and angle and pulmonary flow distribution were the independent predictors of HFD across TCPC templates.…”
Section: The Key Drivers Of Hepatic Flow Distributionmentioning
confidence: 96%
“…The resistances of completed patient-specific TCPCs were shown to account for 15-20% of the PVR at rest. 12,37 When included in an albeit simple lumped parameter model of the Fontan circulation, higher resistance TCPCs significantly limited the ventricular preload, leading to a blunted increase in cardiac output with heart rate suggesting a limited exercise capacity. 37 But it was only very recently that clinical relationships were established demonstrating that TCPC iPL were negatively correlated to aerobic threshold for exercise 19 and to resting ventricular end-diastolic and stroke volumes.…”
Section: Patient-specific Simulations Of the Fontan What Have We Leamentioning
confidence: 99%
See 1 more Smart Citation